Rebranding Pusat Perbelanjaan Star Department Store sebagai Upaya Penyelamatan Bisnis - Ayumi Isidah; Dwi Purbaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the rebranding strategy implemented by Star Department Store as a step to save the business amidst the increasingly tight competition in the retail industry. The traditional shopping center industry faces major challenges due to changes in consumer behavior, advances in digital technology, and the impact of the COVID-19 pandemic which has changed people's shopping patterns. Star Department Store, as one of the old players in the Indonesian retail industry, implemented a comprehensive rebranding strategy to maintain its existence and regain consumer trust. This study uses a qualitative approach with a case study method to analyze the rebranding process carried out by Star Department Store. Data were collected through in-depth interviews with company management, field observations, and analysis of company documents. Theories of marketing communication, brand identity, and crisis management are used as theoretical bases to analyze the effectiveness of the rebranding strategy implemented. The results of the study indicate that the rebranding of Star Department Store to Rambla Department Store includes changes in visual identity, physical store renovation, product diversification, and digital transformation through an e-commerce platform. An integrated marketing communication strategy was implemented to introduce the new brand image to a wider target market, including millennials and Gen Z. The rebranding implementation also involved improving customer experience through digital technology and more responsive customer service. This study shows that the rebranding strategy is effective in increasing brand awareness and getting a positive response from consumers. However, challenges still exist related to consistency in implementing the new brand identity and adapting to changing technological developments. The recommendations produced include the importance of long-term commitment in implementing the rebranding, ongoing investment in digital technology, and systematic evaluation to measure the effectiveness of the rebranding strategy.